ADOPTION OF IMPROVED FARM PRACTICES AMONG MAIZE (Zea mays L) FARMERS IN YOLA, ADAMAWA STATE, NIGERIA - Augustine Anthony NDAGHU; Maimuna MUKTHAR; Amurtiya MICHAEL (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Maize (Zea mays L) is among the most widely consumed staples and is also used in the production of livestock feeds. This study analysed the adoption of improved farm practices among maize farmers in Yola, Adamawa State, Nigeria. The specific objectives were to; describe the socio-economic characteristics of the respondents, identify the improved farm practices adopted by the respondents, and identify respondents’ sources of information on improved farm practices. Systematic random sampling technique was used to select 117 respondents from whom primary data was collected using structured questionnaire. The data collected was analysed using means, frequency and percentages. The result showed that, majority (67.5%) of the respondents were male, married (76%), educated (70%), and 54.6% were within the economically active age of less than 51 years. Majority (81%) of the respondents were small scale farmers with land holdings of 1-4 ha, 77% of the respondents practiced maize farming for more than 10 years, 56.4% and 43.6% practiced sole cropping and mixed cropping respectively. Radio, friends, and extension agents were most preferred information sources. Use of herbicides, fertilizers, seed dressing, and mechanized farming were respondents’ most adopted improved technologies. The study recommends that radio should be used to disseminate information on improved farm practices; farmers should also, be encouraged to form groups that would assist them share information and pool resources together to overcome transitional cost of certain technologies.